(untitled) (Praxis Educativa, 2018)
After ten years of publication of the "Manifesto for education" we can affirm that it did not seek to be a model for the future of education nor was it conceived to be, but nevertheless tried to express something "about" education and something "for" The education. In that sense, the "Manifesto" tried to express real and incessant concerns, for which "it is worth fighting," whenever we consider that "fighting" is perhaps too strong a notion in a world characterized by tension and conflict. In the lines that are expressed below, we share some reflections about said manifesto, being aware that its traces and concerns are latent in those who consider education as a space of complete freedom.